PERJANJIAN ANTARA PENGEMUDI GO-JEKDENGAN PEMILIK PROVIDERGO-JEK (STUDI TERHADAP HAK DAN KEWAJIBAN PARA PIHAK DALAM PERJANJIAN) (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
This study discusses the Agreement Between GO-JEK Drivers and GOJEKProvider Owners (Study of the Rights and Obligations of the Parties in theAgreement) ". A covenant is an act by which one or more people committhemselves to one or more other people. Based on Article 1338 of the CivilCode which reads: "All treaties made legally apply as a law for those whomake them". The agreements cannot be withdrawn other than by the agreementof the two parties, or for reasons stated by law to be sufficient for that. Thepurpose of this thesis is; First, to find out the fulfillment of GO-JEK driver'srights and obligations with the owner of the GO-JEK provider in a partnershipagreement based on justice; Second, to find out efforts to resolve disputes onthe rights and obligations of the go-jek driver with the go-jek provider in apartnership agreement based on justice. The type of legal research used by thewriter is normative legal research or library research.The type of legal research used by the writer is normative legalresearch or library research. Normative legal research uses primary data andsecondary data. Data collection techniques in this research is the study ofliterature that is the author takes quotes from reading books, literature, orsupporting books that have a relation with the problem to be studied.From the results of this study the author concluded that the legalprotection of the rights and obligations of GO-JEK drivers with GO-JEKprovider owners based on partnership agreements has not been fullyimplemented properly. The contents of the partnership agreement areunilaterally determined by the obligations of the GO-JEK driver. GO-JEKDrivers do not have the right to give consideration to the partnershipagreement so that it is not beneficial to the parties, especially GO-JEKDrivers, not. So that the rights and obligations in the GO-JEK partnershipagreement have not been fulfilled. Settlement of GO-JEK driver's rights andobligations disputes with the owner of the GO-JEK provider in the firstpartnership agreement through consultation and the second through court.Settlement of disputes through deliberation in practice has not gotten maximumresults so that the parties to the dispute have not got the rights and obligationsproportionally.Keywords: GO-JEK Driver-Agreement-GO Provider GO-JEK